2020
DOI: 10.1063/1.5142592
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling controlling factors of the S/S1 minimum energy conical intersection (2): Application to penalty function method

Abstract: Minimum-energy conical intersection (MECI) geometries play an important role in photophysics, photochemistry, and photobiology. In a previous study [Nakai et al., J. Phys. Chem. A 122, 8905 (2018)], frozen orbital analysis at the MECI geometries between the ground and first electronic excited states (S0/S1 MECI), which considers the main configurations contributing to the excitation, inductively clarified two controlling factors. First, the exchange integral between the highest occupied molecular orbital (HOMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 77 publications
3
13
0
Order By: Relevance
“…The SF‐TDDFTB and SF‐TDLCDFTB methods drastically reduced the computational cost with improved accuracy for MECI structures compared with SF‐TDDFT. Furthermore, as shown in our previous study obtained by SF‐TDDFT, the SF‐TDDFTB and SF‐TDLCDFTB calculations indicated the controlling factors, that is, K HL ≈ 0 at S 0 / S 1 MECIs.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The SF‐TDDFTB and SF‐TDLCDFTB methods drastically reduced the computational cost with improved accuracy for MECI structures compared with SF‐TDDFT. Furthermore, as shown in our previous study obtained by SF‐TDDFT, the SF‐TDDFTB and SF‐TDLCDFTB calculations indicated the controlling factors, that is, K HL ≈ 0 at S 0 / S 1 MECIs.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, we verified the controlling factors of S 0 / S 1 MECI discovered in our previous studies at the SF‐TDDFTB and SF‐TDLCDFTB levels. Figure shows the HOMO−LUMO exchange integral, K HL , of Equation in hartree for S 0 EQ and S 0 / S 1 MECI structures of 29 molecules.…”
Section: Illustrative Applicationssupporting
confidence: 86%
See 2 more Smart Citations
“…Its accuracy is reportedly comparable to that of conventional ab initio electronic structure methods (including SF-TD-DFT), but its computational cost is several orders of magnitude lower. 20,27 The root of the second difficulty, that is, the high computational cost, is the high-order scaling of the computational time required for typical excited-state calculation methods with system size. Traditionally, this type of problems has been treated by molecular-mechanical (point-charge) description of the solvent molecules, or continuum solvation models, for example, the polarizable continuum model, the conductor-like screening model, and the generalized Born model.…”
Section: Introductionmentioning
confidence: 99%